الاحتلال الإيطالي وأثره على التكوين التعليمي في المجتمع الليبي1911- 1943م (Journal of Humanitarian and Applied Sciences, 2023)
We begin this research by asking several questions that the researcher have thought of, and I try as much as possible to find a comprehensive and adequate answer to them. Were the Italian calls for the occupation of Libya under the slogan of defending Italian interests, protecting the members of its community, as well as moving this country from a state of poverty, disease, and illiteracy? Is the denial of opportunities for modern education embodying that goal, or does it disprove and invalidate its false claims? Did the Italian language and culture impose the road to reach the backbone of Western civilization, or was the goal of separating the Libyan people from their language and culture and cutting off their communication with the people of their Arab nation? Why did the Italians restrict the completion of higher education, making it the preserve of their fellow settlers? Did the Italian authorities prepare a practical program that serves the education sector, overcome the obstacles standing in its way and serves the people of Libyan society, and works on their awareness and development, or did they want it to be the means to achieve the goal of passing on their plans based on the remembrance of Libyan society, and transforming their loyalty to it from school to home, the street, the village and the city, so that it may be a channel for the reception of Western culture through its children, who will absorb its ideas and slogans?